Peripheral iridectomy in descemet stripping endothelial keratoplasty: to do or not to do - Kumar, Santosh; Singh, Roohie (International Journal of Advances in Medicine, 2020)
Background: The purpose of the research was to study role of peripheral iridectomy (PI) in alleviating intra ocular pressure (IOP) spike due to retained air in patients of pseudophakic bullous keratopathy (PBK) undergoing descemet stripping endothelial keratoplasty (DSEK). Methods: A retrospective case review was done for patients undergoing DSEK at tertiary care eye centre from January 2017 to December 2018. Patients were divided into two groups based on whether they have undergone PI during DSEK surgery or not. Total 25 patients were included in the study. Group 1 consisted of 15 patients who hadn’t undergone PI and group 2 consisted of 10 patients who had undergone PI. Study of post-operative IOP spike was done in all cases and role of PI was evaluated. The primary outcome measure was role of PI in alleviating IOP rise. Statistical analysis was done using statistical package for social sciences (SPSS) statistical software version 26.0. Results: All patients in group 1 had developed an IOP spike on first post-operative day. The mean IOP on day 1 in group 1 patients were 29±2.9 mm of Hg (range 24-34 mm of Hg) and in group 2 were 19±1.49 mm of Hg (range 17-21 mm of Hg). Almost all patients in group 1 required anti glaucoma medications. Group 2 had better post-operative results as compared to group 1in terms of best corrected visual acuity (BCVA) as well as graft clarity. Three patients in group 1 had to undergo repeat DSEK. Conclusions: DSEK surgery causes increase in IOP post operatively due to retained air in anterior chamber (AC), probably causing pupillary block. PI definitely has some role in alleviating this IOP spike and increasing graft survival in long term.